1999
DOI: 10.1152/ajpregu.1999.277.3.r742
|View full text |Cite
|
Sign up to set email alerts
|

Leptin alters metabolic rates before acquisition of its anorectic effect in developing neonatal mice

Abstract: Leptin inhibits food intake and increases metabolic rates in adult mice. Neonatal mice need to maximize food intake and also maintain high thermoregulatory metabolic rates to optimize survival, suggesting that leptin may function differentially in neonatal versus adult animals. The efficacy of exogenous leptin to alter these two physiological functions during development was thus examined in C57BL/6J lean (+/+ or ob/+) and ob/ ob(leptin-deficient) mice. Intraperitoneal leptin administration (1 mg/kg body wt) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
135
8
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 20 publications
15
135
8
2
Order By: Relevance
“…The high levels of ir-leptin that we found in mares' colostrum and transitional milk are consistent with the suggestion of Mistry et al [19] that the peptide's thermoregulatory role in the neonate differs from the anorectic role in adults, acquired most likely at the time of weaning.…”
Section: Milk Constituents and Hormone Determinationssupporting
confidence: 92%
See 1 more Smart Citation
“…The high levels of ir-leptin that we found in mares' colostrum and transitional milk are consistent with the suggestion of Mistry et al [19] that the peptide's thermoregulatory role in the neonate differs from the anorectic role in adults, acquired most likely at the time of weaning.…”
Section: Milk Constituents and Hormone Determinationssupporting
confidence: 92%
“…Emerging evidence has indicated that leptin in milk may be involved in the regulation of growth, and in particular in the development and maturation of the neonatal gut, the immune system and the neuroendocrine system [12,24]. Leptin in milk may also exert a more general regulatory activity until organ systems begin to function autonomously [19].…”
Section: Introductionmentioning
confidence: 99%
“…In newborn rodents, a peak of leptin appears during the second week of life, which is not related to the regulation of food intake (Ahima et al 1998, Mistry et al 1999, Proulx et al 2002. This peak has been related to a maternal origin through lactation (Stocker et al 2004, Bautista et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 At this stage, leptin regulates metabolic rate and hypothalamic neuropeptides expression, but not food intake. [19][20][21] These observations could be, at least partially, explained by the kinetic in the development of neuronal hypothalamic network, which begins in rodents only after birth (day 6) to be achieved at the end of the second postnatal week. 22 During that temporal window, neuronal projections are developing to interconnect the different hypothalamic nuclei responsible for food intake regulation, and leptin appears to play a crucial role in this phenomenon.…”
Section: Introductionmentioning
confidence: 99%